Architectural Intelligence Selected Papers from the 1st International Conference on Computational Design and Robotic Fabrication (CDRF 2019) - Yuan, Philip F.; Xie, Mike.; Leach, Neil.; Yao, Jiawei; Wang, Xiang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This book presents selected papers from The 1st International Conference on Computational Design and Robotic Fabrication (CDRF 2019). Focusing on novel architecture theories, tools, methods, and procedures for digital design and construction in architecture, it promotes dialogs between architecture, engineer, computer science, robotics, and other relevant disciplines to establish a new way of production in the building industry in the digital age. The contents make valuable contributions to academic researchers and engineers in the industry. At the same time, it offers readers new ideas for the application of digital technology.
Section 1: Material Intelligence -- Material Agency -- Material Performance -- Interactive Environment -- Section 2: Data Intelligence -- Data Gathering -- Simulation and Optimization -- Information modelling.Section 3: Computational Intelligence -- Generative Morphology -- Design Neural Networks -- AI Design -- Section 4: Robotic Intelligence -- Automated Fabrication -- Robotics -- Human-Machine Collaboration.
Keywords: Control engineering; Robotics; Automation; Computer-aided engineering; Computer simulation; Control, Robotics, Automation; Computer-Aided Engineering (CAD, CAE) and Design; Computer Modelling; Robotics